Enhancing Graduate Competitiveness through Reward and Recognition: A Case Study at Guangxi University of Foreign Languages - Li Kun Mei; Aan Komariah; Eka Prihatin; Johar Permana (AL-ISHLAH: Jurnal Pendidikan, 2025)
This study explores the role of reward and recognition in talent management training at Guangxi University of Foreign Languages (GUFL) and their impact on enhancing graduate competitiveness, particularly in the field of language education. Reward and recognition are recognized as key drivers of individual motivation and performance in training environments. A descriptive qualitative approach was employed to gain in-depth insights into the implementation of reward systems in GUFL’s training programs. Data were collected through interviews with 24 educators and 1 student, focusing on experiences with financial rewards, formal recognition, and their perceived effectiveness. Findings indicate that financial rewards significantly boost trainee motivation, while non-financial recognition, such as industry-recognized certifications, increases trainees’ confidence and competitiveness in the global job market. The study also highlights the importance of aligning reward and recognition systems with industry needs and cultural values, particularly within the Southeast Asian context. The results suggest that a well-structured, culturally adaptive, and industry-relevant reward system plays a crucial role in enhancing the quality of talent training and in producing globally competitive graduates. Institutions in similar contexts are encouraged to adopt holistic reward strategies that integrate both motivational and professional development elements.